Increased recurrent falls experience in older adults with coexisting of sarcopenia and knee osteoarthritis: a cross-sectional study - Iijima, Hirotaka; Aoyama, Tomoki (BMC geriatrics, 2021)
Sarcopenia and knee osteoarthritis (OA) are two major risk factors for falls in older adults. The coexistence of these two conditions may exacerbate the risk of falls. This cross-sectional study aimed to test the hypothesis that older adults with coexisting sarcopenia and knee OA displayed an increased risk of falls experience. Participants recruited from an orthopedic clinic were divided into four groups according to the presence of sarcopenia and radiographic knee OA: isolated sarcopenia, isolated knee OA, sarcopenia + knee OA, and control (i.e., non-sarcopenia with non-OA) groups. We used questionnaires to assess falls experience in the prior 12 months. We performed logistic regression analyses to evaluate the relationship between the four groups and falls experience. Of 291 participants (age: 60-90 years, 78.7% women) included in this study, 25 (8.6%) had sarcopenia + knee OA. Participants with sarcopenia + knee OA had 4.17 times (95% confidence interval: 0.84, 20.6) higher odds of recurrent falls (≥2 falls) than controls after adjustment for age, sex, and body mass index. The increased recurrent falls experience was not clearly confirmed in participants with isolated sarcopenia and isolated knee OA. People with coexisting of sarcopenia and knee OA displayed increased recurrent falls experience. This study suggests a new concept, "sarcopenic knee OA", as a subgroup associated with higher risk of falls, which should be validated in future large cohort studies. Not applicable.